Differences in the effects of contrast agents on kidney injury and inflammatory response between diabetic and non-diabetic patients and their clinical significance: CAN in diabetic and non-diabetic patients - Xie, Chunqiao; Liu, Yanjun; Wang, Qi; Wu, Jiakuan (Cellular and Molecular Biology, 2024)
With the increasing incidence of coronary heart disease (CHD), contrast-associated nephropathy (CAN) caused by contrast agents required in coronary angiography has gradually become a clinical concern that needs to be solved urgently. At present, CAN has become one of the most common causes of hospital-acquired acute kidney injury, which seriously affects the prognosis and health of patients. How to effectively identify high-risk CAN patients and prevent the occurrence of CAN has become a hotspot of clinical research. In this study, we attempted to evaluate the effect of contrast agents on renal injury in diabetes mellitus (DM) and non-DM patients by observing some indexes of early renal injury and inflammatory factors, so as to provide a more comprehensive reference for early identification of CAN in the future. The results showed that compared with non-DM patients, contrast agents caused more obvious renal damage in DM patients and more significantly activated inflammatory responses, increasing the risk of CAN. Cystatin C (CysC), neutrophil gelatinase-associated lipocalin (NGAL), C-reactive protein (CRP), and neutrophil-lymphocyte ratio (NLR) all showed excellent predictive effects for the occurrence of CAN after coronary angiography in both DM and non-DM patients.